Distribution and drug resistance of pathogenic bacteria isolated from cancer hospital in 2013 - Liu, Linjuan; Li, Qi; Zhang, Qingyun; Wang, Guohong; Xu, Guobin; Zhang, Ji (Chinese Journal of Cancer Research; Vol 26, No 6 (December 30, 2014): Chinese Journal of Cancer Research, 2014)
Objective: To understand distribution and drug resistance of pathogenic bacteria from a specialized cancer hospital in 2013 in order to provide a basis for rational clinical antimicrobial agents. Methods: Pathogenic bacteria identification and drug sensitivity tests were performed with a VITEK 2 compact automatic identification system and data were analyzed using WHONET5.6 software. Results: Of the 1,378 strains tested, 980 were Gram-negative bacilli, accounting for 71.1%, in which Klebsiella pneumonia, Escherichia coli and Pseudomonas aeruginosa were the dominant strains. We found 328 Gram-positive coccus, accounting for 23.8%, in which the amount of Staphylococcus aureus was the highest. We identified 46 fungi, accounting for 4.1%. According to the departmental distribution within the hospital, the surgical departments isolated the major strains, accounting for 49.7%. According to disease types, lung cancer, intestinal cancer and esophagus cancer were the top three, accounting for 20.9%, 17.3% and 14.2%, respectively. No strains were resistant to imipenem, ertapenem or vancomycin. Conclusions: Pathogenic bacteria isolated from the specialized cancer hospital have different resistance rates compared to commonly used antimicrobial agents; therefore antimicrobial agents to reduce the morbidity and mortality of infections should be used.